Василий Морозов - Ковычева Елена Ивановна (Удмуртия, 2013)
Экземпляры: Ф. 4 (20190903) / Инвентарный номер: 45168 / Цена: 100.00 / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: М 80 / ГРНТИ: 18.31.31 / ББК: 85.143(2Рос.Удм)